Analysis of an Indonesian food bank sustainability using system dynamics simulation - Salsabila Izzati Syalianda; Ratih Dyah Kusumastuti (Institute for Advanced Science Social, and Sustainable Future, 2023)
Foodbank is an organization that obtains food from donor organizations and individuals, proceeds the donated food products at storage facilities and distributes them to the end users, either directly or indirectly via charitable institutions. Foodbanks have been developed in several countries to tackle food waste and hunger problems. This research uses the case of FoodCycle Indonesia (FCI) as one of the food banks in Indonesia that has been in operation since 2017. The purpose of this study is to analyze the sustainability of FCI using system dynamics simulation to identify the factors that influence its sustainability. We develop the initial model based on literature and modify it according to interview results with representatives from FCI and its two partners (charitable organizations that redistribute the donated food to beneficiaries). The model consists of partners, wedding partners, food redistribution, transportation cost, community, volunteers, beneficiaries, and food balance subsystems. Based on the simulation results it can be concluded that FCI will be sustainable as long as the growth of the food supply is constant, and the organization has the financial ability to support the distribution of donated food to the beneficiaries.